Measured and Perceived Exercise Intensity During the Performance of Single-Task, Cognitive-Motor Dual-Task, and Exergame Training: Transversal Study - Matthieu Gallou-Guyot; Anaick Perrochon; Romain Marie; Maxence Bourgeois; Stephane Mandigout (JMIR Publications, 2023)
BackgroundThe physical and cognitive loads borne during exergaming may differ from more conventional cognitive-motor dual-task trainings. ObjectiveThe aim of this pilot transversal study was to compare objectively measured and perceived exercise intensity during exergame, cognitive-motor dual-task, and single-task training sessions. MethodsWe recruited apparently healthy young adults who carried out one session of each type of training: exergaming, cognitive-motor dual-tasking, and single-tasking. We used a custom-made exergame as support. The sessions lasted 30 minutes, were spaced at least 24 hours apart, and took place in random order for each group of 4 participants. We used heart rates to assess exercise intensity and the modified Borg scale to assess perception of intensity. In all, 16 apparently healthy young participants carried out all sessions. ResultsThere was no difference between the different types of training in mean heart rates (P=.27), peak heart rates (P=.50), or Borg scale scores (P=.40). Our custom-made exergame's objectively measured and perceived physical load did not differ between cognitive-motor dual-task and single-task training. ConclusionsAs a result, our exergame can be considered to be as challenging as more traditional physical training. Future studies should be conducted in older adults with or without cognitive impairments and incorporate an assessment of cognitive performance.